(untitled) (Al-Academy, 2017)
The research entitled: (The Constructive Mutation of installation Systems in the Artworks of the artist Ali Al-Najar) has dealt with the concept of Mutation and its systematizations in installation in the artworks of (Ali Al-Najjar). The research has four chapters: The first Chapter deals with the methodological framework represented by the basic problem of the research, that is concerned with the constructive mutation of installation systems. The research aims at finding out the constructive mutation of installation systems in the artwork of ( Ali al-Najar). The research is limited by analyzing visual samples of (Ali Al-Najjar) artworks betwen (1967-1991) The second chapter deals with the theoretical framework, it has five sections. the first one studies the installation systems in art (historical referense), the second one deals with the technical mutation and the intellectual and technological development and their connections with painting, the third section concerns with the of constructive mutation in International contemporary Painting, While The fourth one deals with the constructive mutation in Iraqi Contemporary Painting, The fifth section: studies The artistic experience of Ali al-Najar. The third chapter deals with the research Procedures, and The Population and Samples of The research which includes three artworks, Then the research tool and the sample analysiz. . The fourth chapter included the conclusions. the researcher has drawn the following conclusions: 1-The artist has adopted the Style of exoticness to express extreme psychological states. the metaphysical construction systems are considered as a representation of hunting opposite spatial moments isolated from realistic subjectivity. 2-The artist depends on construction Systematization after insighting The spatial formation of the shape. The mutation from the past & preseat to the future has been achieved by gathering of negative reality supported by ranishing the formative structure and promoting to metaphysics